Evaluating the Effectiveness of PBB-P2 Administrative Modernization on Taxpayer Compliance Levels in Bantul Regency - Darmawan Purwana; Baldric Siregar; Miswanto Miswanto; Frasto Biyanto (Dhana, 2026)
This study aims to examine the impact of digital transformation in the management of Rural and Urban Land and Building Tax (PBB-P2) on taxpayer compliance in Bantul Regency. The modernization studied includes the digitization of payment channels, database system updates, and innovation in tax services. A quantitative approach was applied, involving 100 taxpayer respondents spread across five sub-districts. Data analysis used multiple regression tests with mediation and moderation approaches. The research findings indicate that administrative modernization has a significant positive influence on taxpayer compliance, both directly and indirectly through increased perceptions of service ease. In addition, taxpayer income levels have been shown to moderate the relationship between modernization and compliance. The implications of these results emphasize that the acceleration of service digitalization needs to be accompanied by strengthening supporting infrastructure and ongoing outreach.